Determinants of capital structure among domestic and foreign commercial banks operating in Malaysia / Muhammad Aslam Maidi - Maidi, Muhammad Aslam (2019)
The motivation behind this paper is to look at the determinants of capital structure among domestic and foreign commercial banks in Malaysia. There are several determinants that may contribute to capital structure decision. Furthermore, this paper focuses only on three factors of commercial banks in Malaysia and tries to find if there is a relationship towards capital structure. The subordinate variable is association's influence proportion and autonomous variables consist of tangibility, profitability and earnings volatility. This paper uses the secondary data information of six listed commercial banks under supervision of Bank Negara Malaysia for the period of 10 years from 2009 to 2018. Finding shows that profitability is the most important determinant of capital structure for commercial banks licensed by Bank Negara Malaysia. Result of theory testing dependent on connection between independent and dependent variables are completely in accordance with the pecking order theory hypothesis, while it mostly supports trade of theory in short, capital structure of Malaysian commercial banks is totally classified by pecking request hypothesis of capital structure.